DIFFERENTIATION OF THE FAGIO N AND LUZULO-FAGION ASSOCIATIONS IN THE CZECH REPUBLIC - MORAVEC, J. (Annali di Botanica, 1997)
The beech woods of the Czech Republic are classified on the basis of their floristic composition into 10 associations of the alliance Fagion and 2 associations of the Luzulo-Fagion. The floristic composition depends mainly on ecological factors (climatic and soil conditions). However, chorological phenomena are also important. The herb layer plays the leading role in the syntaxonomic differentiation of associations and alliances.